Analysis Of The Chassis And Components Of All Terrain Vehicle (ATV) - Abdullah, Mohd Azman; Tamaldin, Noreffendy; Ramli, Faiz Redza; Sudin, Mohd Nizam; Mohamed Muslim, Abdul Mu'in (Trans Tech Publications, 2014)
-